2013
DOI: 10.1179/2045772313y.0000000132
|View full text |Cite
|
Sign up to set email alerts
|

Functional assessment and performance evaluation for assistive robotic manipulators: Literature review

Abstract: Context:The user interface development of assistive robotic manipulators can be traced back to the 1960s. Studies include kinematic designs, cost-efficiency, user experience involvements, and performance evaluation. This paper is to review studies conducted with clinical trials using activities of daily living (ADLs) tasks to evaluate performance categorized using the International Classification of Functioning, Disability, and Health (ICF) frameworks, in order to give the scope of current research and provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 28 publications
0
67
0
1
Order By: Relevance
“…Two buttons are used to select whether to move the hand position (mode 1), its orientation (mode 2) or the fingers (mode 3). The GUI was developed with Qt and is open-source 4 . Both interfaces use the same Kinova API for robot control and inverse kinematics solving.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two buttons are used to select whether to move the hand position (mode 1), its orientation (mode 2) or the fingers (mode 3). The GUI was developed with Qt and is open-source 4 . Both interfaces use the same Kinova API for robot control and inverse kinematics solving.…”
Section: Methodsmentioning
confidence: 99%
“…Guo & Sharlin noted that preferences for a tangible interface was related to a stronger performance in using it [15]. Many studies on control interfaces for robots focused on graphical user interfaces for their better acceptance by non-experts, for example [6] for teaching objects to a robot, [4] for applications in rehabilitation and medicine. In [5] the authors proposed an Android interface for moving the Jaco arm, but unfortunately it was not thoroughly evaluated by final users.…”
Section: Introductionmentioning
confidence: 99%
“…The user triggers the task by fixating on a recognised object. According to [18], meal preparation and drink retrieval were considered top desired tasks for disabled patients. It was decided that the automatic mode should incorporate these functions.…”
Section: F Operation Modesmentioning
confidence: 99%
“…Removing the fixation requirement of 2s and the ROS node sleep rate of 1s, the average time to determine the user's 3D fixation point and to plan a valid path is 6.92s. Although activation time is an important aspect for a Human-Robot Interaction system, studies showed that patients did not feel the time to complete the task was significant, but rather they are content with being able to perform the task independently [18].…”
Section: B Trajectory Planning Performancementioning
confidence: 99%
“…The primary physical UIs of commercial ARMs, including a 4x4 keypad 7 and 3-axis joystick, 8,9 provide robotic control for Cartesian, joint, and finger movements. 10 Previous studies demonstrated their cost-effectiveness and long-term usage. 4,11,12 The joystick has 3 degrees of freedom allowing horizontal and twisting movement.…”
mentioning
confidence: 99%